2015
DOI: 10.1177/1066480715601110
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ and Fathers’ Sensitive Parenting and Mother–Father–Child Family Alliance During Triadic Interactions

Abstract: Observing parent–child dyadic interactions has helped researchers understand how maternal and paternal parenting contributes to child development, whereas the study of mother–father–child triads has documented the role of family-level relations. Dyadic and triadic interactions have rarely been observed, however, within the same families in a single study. This study aimed to investigate how the quality of parenting, in terms of parental sensitivity, influenced or was influenced by the quality of family allianc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
2
9
2
Order By: Relevance
“…The finding that nuclear family triadic interactional synchrony was associated with mother–child and father–child interactional synchronies confirms our hypothesis concerning the active contribution of mother–child and father–child dyadic interactions to the family triad at the child’s third year. However, in contrast to similar studies showing that mothers exert a greater influence than fathers on triadic family relationships during the first year of the child’s life (e.g., Tissot et al, 2015), and contrary to our hypothesis, our results indicated a greater association between father–child interaction and family triadic interactional synchrony.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The finding that nuclear family triadic interactional synchrony was associated with mother–child and father–child interactional synchronies confirms our hypothesis concerning the active contribution of mother–child and father–child dyadic interactions to the family triad at the child’s third year. However, in contrast to similar studies showing that mothers exert a greater influence than fathers on triadic family relationships during the first year of the child’s life (e.g., Tissot et al, 2015), and contrary to our hypothesis, our results indicated a greater association between father–child interaction and family triadic interactional synchrony.…”
Section: Discussioncontrasting
confidence: 99%
“…According to the authors, fathers’ behavior in the triad may be inhibited by a high level of mother–child mutual engagement in the triadic context. In addition, Tissot et al (2015) demonstrated that when infants were 3 months old, parental sensitivity of both mothers and fathers predicted a cooperative family alliance in the triad, whereas only mothers’ sensitive parenting predicted positive triadic family interactions when the child was 9 months old. Moreover, when the child was 18 months old, neither maternal nor paternal sensitivity accounted for a cooperative family alliance in the triad, raising questions concerning other mechanisms and processes that could influence the family triadic social interaction as the child grows older.…”
Section: The Relationship Between the Nuclear Family Triad And Other mentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly, Gueron-Sela et al (2015) measured family alliance using the Lausanne Trilogue Play scenario (Corboz-Warnery, Fivaz-Depeursinge, Gertsh Bettens, & Favez, 1993), which measures the appropriateness of affect sharing, family warmth, and validation of a child’s emotional experience in the triad, whereas our measure of quality of attachment was a survey measure. Although family alliance and attachment are related (Tissot, Favez, Udry-Jorgensen, Frascarolo, & Despland, 2015), this might explain some of the variation in our findings as compared to previous studies. However, we used a similar emotional distress measure to that of Gueron-Sela et al (2015) and did not find the same parental emotional distress results, suggesting the differences are not entirely due to differences in measurement.…”
Section: Discussioncontrasting
confidence: 61%
“…This is partly in line with earlier studies among younger children which found that parenting of mothers had stronger influences on their child's development than parenting of fathers (e.g., Ruiz-Ortiz, Braza, Carreras & Muñoz, 2017;Tissot, Favez, Udry-Jorgensen, Frascarolo & Despland, 2015). Contradictory, other studies among younger children (e.g., Meuwissen & Englund, 2016;Tissot et al, 2015) and adolescents (e.g., Dekovi c & Buist, 2005) found that both parents have a similar influence on their child's development or that fathers have stronger influences on adolescents' development than mothers (e.g., Buist, Dekovi c & Gerris, 2011;Dekovi c & Buist, 2005;Ruiz-Ortiz et al, 2017). However, most of these studies focused on parenting rather than parent-child relationship quality.…”
Section: Discussionsupporting
confidence: 90%